Central Tax Evolution In Indonesia And Islamic Economic Perspective Central Tax - Choirunnisak Choirunnisak (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
This study examines how the evolution or development of Central Tax in Indonesia and how the Central Tax is from an Islamic economic perspective. Descriptive analysis and qualitative data collection were used in this library-based study. This study finds that the current central tax in Indonesia is a development of the tax system that existed since the kingdom era. In the era of the tax empire called "UPETI". Currently, the central tax is managed by the Directorate General of Taxes (DGT) which is under the Ministry of Finance of the Republic of Indonesia and is tasked with developing and enforcing policies that promote technical standardization in the taxation system. Taxes from an Islamic economic perspective are known as jizyah, kharaj and 'ushr.